The Ius Constituendum of Inter-agency Synergy Arrangements Related to Natural Disaster Mitigation and Action - Pramono, Joko; Wangi, Maya Sekar; Setiodjati, Josef Purwadi; Kusumastuti, Dora; Ibrahim, Ahmad Zubir (SASI, 2023)
Introduction: Natural disasters cause resource destruction and social threats. The synergy of important institutions is facing impact. Indonesia is prone to natural disasters due to volcanic eruptions, earthquakes, etc. Climate change and urbanization are exacerbating the situation. Effective law is needed, including institutional synergy, for disaster mitigation and prosecution.Purposes of the Research:  To gain a deeper understanding of inter-agency synergies in dealing with natural disasters in Indonesia, as well as to contribute to the development of a better and more effective legal framework for mitigating and overcoming natural disasters. Implementation of a more solid and coordinated legal framework is expected to increase the efficiency and effectiveness of natural disaster mitigation and prosecution efforts.Methods of the Research: This study uses a qualitative normative research method with a statutory approach. The collection of legal materials involves laws, government regulations, regional regulations, government policies, court decisions, as well as legal literature such as articles, journals and books. The analysis is carried out by identifying and selecting relevant regulations, categorizing issues related to institutional roles, resources, and responsibilities.Results of the Research: Synergy between agencies is the main key in a rapid and coordinated response to natural disasters. Several related institutions have been assigned to deal with disasters, but the implementation of existing laws and regulations needs to be evaluated and improved. In facing this challenge, the Ius Constituendum concept can be applied to strengthen inter-agency synergies related to natural disaster mitigation and prosecution. In implementing the Ius Constituendum concept, the involvement of all stakeholders and an intensive dialogue process are very important to ensure that the laws and regulations that are implemented are in accordance with the needs and conditions that are developing. By formulating and implementing the Ius Constituendum concept correctly, inter-agency synergy in managing natural disasters in Indonesia can be increased.